2012
DOI: 10.1007/s00330-012-2378-5
|View full text |Cite
|
Sign up to set email alerts
|

MR relaxometry of the liver: significant elevation of T1 relaxation time in patients with liver cirrhosis

Abstract: • Significantly elevated magnetic resonance T1 relaxation times are found in liver cirrhosis. • T1 relaxation times can distinguish healthy subjects from patients with liver cirrhosis. • T1 relaxation times can distinguish Child-Pugh classes Aand B from C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 39 publications
9
77
0
Order By: Relevance
“…In addition, the diagnostic capability of T1 relaxometry was compared with a previously validated blood test (APRI) for diagnosing cirrhosis. Pre-contrast T1 relaxation time for non-cirrhotic livers (610 ± 81.6 msec) was comparable to previously published data at 1.5 T [27][28][29]. Assessment of liver fibrosis and cirrhosis and liver function is important for diagnosis and for assessing the prognosis of patients with chronic liver diseases, and is particularly required in cirrhotic patients to determine the optimal timing for liver transplantation and before liver resection for hepatocellular carcinoma to minimize the risk of post-operative liver failure.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the diagnostic capability of T1 relaxometry was compared with a previously validated blood test (APRI) for diagnosing cirrhosis. Pre-contrast T1 relaxation time for non-cirrhotic livers (610 ± 81.6 msec) was comparable to previously published data at 1.5 T [27][28][29]. Assessment of liver fibrosis and cirrhosis and liver function is important for diagnosis and for assessing the prognosis of patients with chronic liver diseases, and is particularly required in cirrhotic patients to determine the optimal timing for liver transplantation and before liver resection for hepatocellular carcinoma to minimize the risk of post-operative liver failure.…”
Section: Discussionsupporting
confidence: 77%
“…For instance, regional variations in hepatic parenchymal tissue composition and nodularity can be readily depicted on hepatic magnetic resonance (MR) images [12,13]. In addition, studies have reported the appropriate characterization of hepatic parenchymal properties using functional MR techniques including MR spectroscopy [14,15], MR elastography [16], diffusion-weighted imaging [17], MR relaxometry [18], and Gd-EOB-DTPA-enhanced MRI [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. In this article, we will review and discuss recently published studies that used Gd-EOB-DTPA-enhanced hepatic MRI to evaluate hepatic function.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, no renal biopsies were performed during this study, prohibiting us from describing the association of prolonged T 1 relaxation times with histopathological findings. Nevertheless, based on the results obtained for other organs [18][19][20][21][22] and the lack of T 1 alterations during acute kidney injury [34], prolonged relaxation times appear to correspond to more severe tissue fibrosis and scaring. Further studies are needed to verify the association of renal T 1 relaxation with parenchymal damage.…”
Section: Discussionmentioning
confidence: 86%
“…Importantly, this older study also assessed three patients with acute renal failure and biopsyproven acute tubular necrosis in which T 1 relaxation times were not prolonged. In addition, T 1 relaxation time has been associated with chronic parenchymal remodelling in animal models of post infarct myocardial scarring [18], knee cartilage in osteoarthritis [19], and biopsy-proven liver cirrhosis [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation